Strategi Pengembangan Pariwisata Berbasis Budaya di Desa Selumbung, Karangasem - M. Agus Sutiarso; K.T. Pratiwi Arcana; N.P. Eka Juliantari; I.M. Bayu Gunantara (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2018)
Selumbung Village is one of the villages that is directed to be developed as a tourist village in Karangasem regency. Culture-based tourism development in this village is expected to provide benefits to the community if properly managed and planned. This study aims to get a recommendation for the strategic plan of cultural-based tourism development in the village of Selumbung. The analytical method used in this study includes descriptive analysis which is assisted by the SWOT analysis method to determine thedevelopment strategy plan. The results showed that the priority of the culturebased tourism development strategy plan in the village of Selumbung was to develop tourism products, improve management and marketing